Risk Factors For Anemia In Pregnant Women In The Third Trimester - Swastika Sari Sakina; Nani Surtinah; Budi Joko Santoso; Agung Suharto (International Journal of Advanced Health Science and Technology, 2024)
Anemia is a condition in which the percentage of erythrocytes and hemoglobin (Hb) levels of pregnant women fall below normal. Ponorogo Regency Health Profile Data in 2022, there were 1,746 anemic pregnant women out of 10,878 (16.50%). This study aims to provide an overview of risk variables and initiatives aiming to decrease the proportion of anemia cases among pregnant women. Method: Analytical observational research was used to conduct the study, which was conducted retrospectively from quantitative data. All 62 pregnant women with anemia in the third trimester formed the study sample for the case population. Two independent (free) factors were used in this study: parity, education, nutritional status, maternal age, and gestational age. The prevalence of anemia in third trimester pregnant women is the dependent variable. The instrument used by researchers is an observation sheet. Data analysis to test the truth of the hypothesis uses Regression Logistic Analysis. Result: The findings of the study revealed that maternal age (p-value 0.009) and gestational age (p-value 0.027) were risk factors that had an impact on the incidence of anemia at the North Ponorogo Health Center, indicating that gestational age affects the incidence of anemia. Maternal age has a significant risk impact on the occurrence of anemia. The data showed that the incidence of anemia with a risk of 0.884 times was not affected by nutritional status (p-value = 0.727), parity (p-value = 0.043), education (p-value = 0.043), while the incidence of anemia with a risk of 8.483 times was influenced by parity. Discussion: The findings of this study lead to the conclusion that influencing risk factors were gestational age, maternal age and parity, while nutritional status and education were risk factors that had no effect on anemia in pregnant women. Suggestion: It is expected to provide advice or reference to health centers in order to conduct early detection or further improve comprehensive examinations in order to reduce the prevalence of anemia in the third trimester of pregnancy among several parameters that have been examined by researchers.